Implementing Organizational Change Management in Company ABC - Wardani, Elisa Kusuma; Hendarman, Achmad Fajar (Journal of Business and Management, 2019)
Company ABC is a private company that working the fast-food sector based in Bandung. The issues occur when the company does not have a good internal management system, implementation of hands-on management style and unclear vision, mission and formulated job description which indicates the organization ineffectivess. This research applied project demonstrated the utilization of the action research model through assessment the problem diagnosis and intervention. The assessment of organizational effectiveness using the star model analysis which assessed five fundamental things in the company which are strategy, structure, reward, process, and people. After identifying organization effectiveness, researcher finds out that the organization hasn’t performed effectively because there’re still many improvements need to be applied. The improvement proposed by designing intervention through transformational change which focus on basic character of organization. In the transformational change, the author will focus on the organization design which configures the organization’s strategy, structure, work design and human resources practices. Keywords: Organization Change Management, Organization Effectiveness, The Star Model, Action Research Model, Transformational Change